Description of a novel termite ectoparasite, Termitaria hexasporodochia sp. nov. (Kathistaceae), presenting an unusual six-sectioned infestation, and a key to the fungal family Kathistaceae - Wilson, Megan M.; Emam, Amany; Davis, Steven R.; Hall, Gene; Barden, Phillip; Ware, Jessica L. (Phytotaxa, 2023)
Termites, an economically significant group of eusocial cockroaches, are host to a variety of ectoparasitic fungi. Here, we provide up-to-date morphological and geographic data for fungal ectoparasites described belonging to the family Kathistaceae and describe Termitaria hexasporodochia sp. nov., a species observed to form lesions on its host in an unusual hexad arrangement. To date, the family Kathistaceae comprises 4 genera (Kathistes, Mattirolella, Termitaria, and Termitariopsis) and 11 valid species. Two genera we focus on in this paper, Termitaria and Mattirolella, are asexual ectoparasitic fungi that form sporodochia on the eusocial insects, termites. Morphological data collected via Micro-CT, SEM, and confocal microscopy confirms that this is a new fungal species belonging to the genus Termitaria. A comparison chart and dichotomous key are provided to distinguish all members of the family, Kathistaceae, to which the new species belongs.